2020
DOI: 10.3390/cancers12010223
|View full text |Cite
|
Sign up to set email alerts
|

MAGI1, a New Potential Tumor Suppressor Gene in Estrogen Receptor Positive Breast Cancer

Abstract: Membrane-associated guanylate kinase (MAGUK) with inverted domain structure-1 (MAGI1) is an intracellular adaptor protein that stabilizes epithelial junctions consistent with a tumor suppressive function in several cancers of epithelial origin. Here we report, based on experimental results and human breast cancer (BC) patients’ gene expression data, that MAGI1 is highly expressed and acts as tumor suppressor in estrogen receptor (ER)+/HER2− but not in HER2+ or triple negative breast cancer (TNBC). Within the E… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
31
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 19 publications
(34 citation statements)
references
References 94 publications
1
31
2
Order By: Relevance
“…The ERK/MAP Kinase and JNK stress kinase pathways could be influenced by junctions and the forces they sense 15,17,18 . In response to MAGI1 loss, we did not detect any alterations of the main oncogenic pathways: ERK1/2, JNK and Akt pathways (Figure 6A&B) in contrast with recently published results on MAGI1 function 45 . Interestingly, the p38 stress kinase was strongly activated in MCF7 shMAGI1 compared to MCF7 shLuc -: the amount of phosphorylated p38, normalized to total p38 protein level, was increased 2 fold (Figure 6A&B) leading to increased p38 activity as evidenced by the elevated expression of the p38 transcriptional target genes 49 ATF3, SOX9, and GATA6 (SOX2 levels remained unchanged) (Figure 6C).…”
Section: Resultscontrasting
confidence: 99%
See 1 more Smart Citation
“…The ERK/MAP Kinase and JNK stress kinase pathways could be influenced by junctions and the forces they sense 15,17,18 . In response to MAGI1 loss, we did not detect any alterations of the main oncogenic pathways: ERK1/2, JNK and Akt pathways (Figure 6A&B) in contrast with recently published results on MAGI1 function 45 . Interestingly, the p38 stress kinase was strongly activated in MCF7 shMAGI1 compared to MCF7 shLuc -: the amount of phosphorylated p38, normalized to total p38 protein level, was increased 2 fold (Figure 6A&B) leading to increased p38 activity as evidenced by the elevated expression of the p38 transcriptional target genes 49 ATF3, SOX9, and GATA6 (SOX2 levels remained unchanged) (Figure 6C).…”
Section: Resultscontrasting
confidence: 99%
“…S1A). Moreover, public database mining (http://www.kmplot) 44 and recent studies 45 , indicated that low MAGI1 expression levels were associated with worse prognosis in relapse-free survival for BCa patients, but only in ER+ (mainly luminal) molecular BCa subtypes (Kaplan Meier curve; Supplementary Fig. S1B).…”
Section: Resultsmentioning
confidence: 97%
“…S1A). Moreover, public database mining ( http://www.kmplot ) 44 and recent studies 45 , indicated that low MAGI1 expression levels were associated with worse prognosis in relapse-free survival for BCa patients, but only in ER+ (mainly luminal) molecular BCa subtypes (Kaplan Meier curve; Supplementary Fig. S1B).…”
Section: Resultsmentioning
confidence: 97%
“…The downstream target genes of miR-484 was predicted using MIRDB, MAGI1 with the highest score was chosen to forsubsequentresearch. Some studies indicated that, in estrogen receptor positive breast cancer, MAGI1 is a new potential tumor suppressor gene [29].Via the Wnt/β-Catenin and PTEN/AKT signaling pathways, MAGI1 silencing inhibited apoptosis of glioma cells and promoted the proliferation [30]. Moreover, via regulating PTEN, MAGI1 curbed invasion and migration of HCC [31].Our study con rmed that MAGI1 was the downstream target gene of miR-484, and TMEM220-AS1 released MAGI1 through competitive binding of miR-484, thereby regulating the progression of HCC.…”
Section: Discussionmentioning
confidence: 99%